MYTHOLOGICALLY RELIGIOUS UNDERSTANDING OF SYMBOL OF CENTRE - Михалевич, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article a role and value of symbol of centre is traced in the culture of before Modern.